2010
DOI: 10.1128/jb.00279-10
|View full text |Cite
|
Sign up to set email alerts
|

Dual Biosynthesis Pathway for Longer-Chain Polyamines in the Hyperthermophilic Archaeon Thermococcus kodakarensis

Abstract: The open reading frames (ORFs) TK0240, TK0474, and TK0882, annotated as agmatine ureohydrolase genes, were disrupted. Only the TK0882 gene disruptant showed a growth defect at 85°C and 93°C, and the growth was partially retrieved by the addition of spermidine. In the TK0882 gene disruptant, agmatine and N 1 -aminopropylagmatine accumulated in the cytoplasm. Recombinant TK0882 was purified to homogeneity, and its ureohydrolase characteristics were examined. It possessed a 43-fold-higher k cat /K m value for N 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 32 publications
(44 reference statements)
0
48
0
Order By: Relevance
“…The aminopropyltransferase of Sulfolobus solfataricus was found to recognize a range of diamines and triamines (92). The variant AdoMet-dependent aminopropylagmatine pathway for Spd biosynthesis, previously identified in the bacterial extreme hyperthermophile T. thermophilus, was found in the euryarchaeote T. kodakaraensis (94).…”
Section: Polyamines In Archaeamentioning
confidence: 98%
“…The aminopropyltransferase of Sulfolobus solfataricus was found to recognize a range of diamines and triamines (92). The variant AdoMet-dependent aminopropylagmatine pathway for Spd biosynthesis, previously identified in the bacterial extreme hyperthermophile T. thermophilus, was found in the euryarchaeote T. kodakaraensis (94).…”
Section: Polyamines In Archaeamentioning
confidence: 98%
“…Agmatine is also a precursor in the synthesis of agmatidine, an agmatine-conjugated cytidine found at the anticodon wobble position of archaeal tRNA Ile (33). Our genetic study revealed that TK0147 and TK0882 encode N 1 -aminopropylagmatine synthase and N 1 -aminopropylagmatine ureohydrolase, respectively, in the production of spermidine (20). Interestingly, larger quantities of agmatine accumulated in strain DAT, in which TK0147 is disrupted, than in the parental KU216 strain.…”
mentioning
confidence: 93%
“…Spermidine and spermine are then produced by the addition of the aminopropyl group from decarboxylated Sadenosylmethionine (dcSAM). In contrast, thermophilic bacteria and archaea possess a unique polyamine biosynthetic pathway, in which spermidine is synthesized from agmatine via N 1 -aminopropylagmatine by aminopropyltransferase, followed by ureohydrolase (18,20,27).…”
mentioning
confidence: 99%
See 2 more Smart Citations